Derivative 11;22 (Emanuel) Syndrome: A Case Report and A Review - Madan Gopal Choudhary; Prashant Babaji; Nitin Sharma; Dilip Dhamankar; Gururaj Naregal; Vijay Sunil Reddy (Case Reports in Pediatrics)
Emanuel syndrome (ES) is a rare anomaly characterized by a distinctive phenotype, consisting of characteristic facial dysmorphism, microcephaly, severe mental retardation, developmental delay, renal anomalies, congenital cardiac defects, and genital anomalies in boys. Here, we report a male neonate, with the classical features of Emanuel syndrome.